DOI: 10.33915/etd.953
|View full text |Cite
|
Sign up to set email alerts
|

Dual fuel conversion of a direct-injection diesel engine

Abstract: First and foremost, I thank Richard Atkinson, the resident electronics guru, for his invaluable guidance and assistance throughout this project. I also extend thanks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…By analyzing the premixed lambda values, it was revealed that there is excess air beyond the flammability limit in this case as shown in figure 14.This might be taken as another reason for the high CO. Obviously by increasing the NG portion, the lambda values decrease as shown in the figure. This can be solved with installing a catalyst in the exhaust system so it can convert most of CO and HC emissions to CO2 and H2O [14,18,19]. As shown from figure 15, the oxygen percent in the exhaust can be used with the catalyst for oxidizing the CO and HC.…”
Section: Engine Exhaust Emissions For Dual Fuel Operation With and Wimentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the premixed lambda values, it was revealed that there is excess air beyond the flammability limit in this case as shown in figure 14.This might be taken as another reason for the high CO. Obviously by increasing the NG portion, the lambda values decrease as shown in the figure. This can be solved with installing a catalyst in the exhaust system so it can convert most of CO and HC emissions to CO2 and H2O [14,18,19]. As shown from figure 15, the oxygen percent in the exhaust can be used with the catalyst for oxidizing the CO and HC.…”
Section: Engine Exhaust Emissions For Dual Fuel Operation With and Wimentioning
confidence: 99%
“…Longer ignition delay and lower concentration of O2 in simple dual fuel modes are the main reasons for the formation of higher CO and HC emissions. The longer ignition delay makes the combustion occurs late in the expansion stroke where there is no sufficient temperature and pressure for achieving complete combustion; so the increase in ignition delay increases the emission of CO and HC [14,18]. Good emission control on dual fuel engines can be achieved by installing a throttle valve and using EGR to get close to stoichiometric operating conditions [14,19].…”
Section: Introductionmentioning
confidence: 99%